KARAKTERISASI BENTONIT PACITAN - Buchari Buchari; Muji Harsini (Jurnal Kimia Terapan Indonesia, 1996)
Bentonite is high plastivity and colloidal clay which contains smectite(montmorillonite) mineral as major the component. Commercially, there are two kinds of bentonite, which are calcium bentonite and sodium ben-tonite. Results of DTA, XRD and IR analysis on Pacitan bentonite, show that the major component is montmorillonite mixed with a little quartz. Cation exchange capacity (CEC), specific gravity, surface area, pore volume and swelling index of this bentonite are 45,98-62.42 meq/100 gram; 2,14-2,28 g/mL; 641,44-737,29 m /gram; 0,88-1,25 mL/gram and 78,95-163,16 %, respectively. Based on XRD and CEC value Pacitan bentonites are of the calcium bentonite type.